Indicators of the cardiovascular system of 7–11 years old girls residing in Northern and Southern Kazakhstan - Tasbulatova, G.S.; Umbetov, A.U.; Sadykova, B.S. (KSU publ., 2020)
Functional characteristics are the leading criterion for assessing the health status of school students’. The body of a schoolchild in its aforementioned signs differs from the body of an adult. Schoolchildren are more sensitive to environmental factors. Physical condition may depend on age, gender, and location. The indicators of the cardiovascular system (CVS) of girls in the ontogenesis of 7–11 years in the city of Pavlodar and Kyzylorda were studied. In the article the results of a study of such indicators as heart rate (HR), systolic and diastolic blood pressure (SBP, DBP) are presented. Based on these data, pulse pressure (PP), double product (DP), reflecting the cost-effectiveness of the cardiovascular system, systolic blood volume (SBV) and minute blood volume (MBV), an indicator of blood circulation efficiency (BCE); Kerdo's vegetative index (KVI), reflecting the vegetative balance are calculated. The adaptation mechanisms and features of the reaction of the cardiovascular system to physical activity are revealed. Under the conditions of performing standard steregometric physical activity, heart rate (HR), double product (DP) of girls have significantly increased compared with the state of rest.
Keywords: cardiovascular system; physical activity; circulatory efficiency; functional indicators of the body; reserves